Vitamin C And E Normalises The Expression Of Sterol Regulatory Element Binding Protein 1c And The Peroxisome Proliferator Receptor In Adipose Tissue Of Pcb-Induced Adult Male Rats - Krishna B, Ashwin; Dinesh, Dinesh (Journal of Neonatal Surgery, 2024)
Background:PCB’s(PolyChlorinated Biphenyls) are hydrogenated aromatic chemicals that are used extensively in making food packages,water bottles and in plastics of toys thus entering the food chain. Vitamin E and C are the two dietary antioxidants which relieve oxidative stress. Aim: The role of vitamin C and E on the expression of SREBP 1C and PPARγ mRNA in PCB-induced in experimental animals. Materials and Method: Male albino wistar rats weighing 180-200 grams were used. Animals were divided into three groups i.e, control group, PCB induced group, PCB induced VitaminC and E treated group consisting of 6 animals each. At the end of treatment the total RNA isolation was done followed by quantification of RNA, cDNA- reverse transcriptase, Quantitative analysis-real time PCR to analyze the mRNA expression levels of SREBP 1C and PPARγ. Data were analysed using one way-ANOVA and significance was considered at the levels of p<0.05. Result:In PCB induced animals there was significant increase in mRNA levels of SREBP 1C conversely PPARγ mRNA expression was found to be significantly increased in PCB exposed rats (p<0.05). PCB-exposed rats treated with antioxidant vitamins normalized the altered levels of mRNA expression to that of the control levels suggesting that antioxidant vitamins (Vit C & E ) have a protective role against PCB-induced detrimental changes in adipose tissue. Discussion: Our present findings show that PCB exposure causes detrimental changes in the adipose tissue which may develop diabetes by modulating the expression ofSREBP-1C and PPARγ . Supplementation of Vitamin C and E have protective roles against PCB-induced changes. Hence, Vitamin C and E can be considered for the treatment of diabetes. Conclusion: Vitamin C and E increases the expression of PPARγ and decreases the expression of SREBP-1C in treated groups and thus reduces lipotoxicity that can reverse insulin resistance. Hence Vitamin C and E can be used as the supplement for diabetes. Studies are needed to further confirm its dosage and mechanism linked to alter the effects of PCB....